PERENCANAAN PROGRAM STRATEGI SANITASI KOTA - A.Rahman Hadi, Mr. (Jurnal Ilmiah Administrasi Publik, 2012)
The purpose of this study were: first, to describe and analyze the planning of programs of City Sanitation Strategy (SSK) in Batu City. Secondly, to describe and analyze the role of the Working Group (Kelompok Kerja/Pokja) Sanitation in the planning of programs the City Sanitation Strategy. Third, describe and analyze the results of the planning programs of the City Sanitation Strategy. Fourth, identify and analyze the factors supporting and inhibiting factors in the planning of programs of City Sanitation Strategy (SSK) Batu City. The research method using qualitative approach to the type deskritif. The source data came from informants and documents. Techniques of data collection through interviews and documentation. Data were analyzed using an interactive model. The conclusion of this study are as follows: (1)Planning programs of urban sanitation strategy is planning, with the top down approach and bottom up in the effort to fulfill community service related to basic sanitation. Technocratic approach, participatory and politically not fully implemented.(2) City Sanitation Working Group was formed through a process of stakeholder mapping and identification, as a driving force to the implementation of ISSDP. Increased capacity and skills of members of the Working Group to be the main thing in the program planning process the city sanitation strategies.(3) Programs and activities as outlined in the document the City Sanitation Strategy (SSK) Batu City prepared by Vision - Mission - Goals, Objectives and Achievements Phasing Direction - the strategic issues - a strategy that had been developed previously. Plan programs and activities apply for 5 years (2010-2014).(4) supporting factors are (a) Support the Central and East Java Provincial Government, (b) Assistance and Capacity Building Working Group Members, (c) Non Governmental Organizations (NGOs), (d) PKK Involvement Cadre. While the inhibiting factors are: (a) lack of human resource planners both in quality and quantity, (b) lack of attention SKPD Head, and (c) Changes in Organizational Structure and Work SKPD.